The Magnitude of Perceived Professionalism and Its Associated Factors Among Nurses in Public Referral Hospitals of West Amhara, Ethiopia - Abate HK; Abate AT; Tezera ZB; Tesgera Beshah D; Agegnehu CD; Getnet MA; Yazew BG; Alemu MT; Mekonenn CK; Kassahun CW (Dove Medical Press, 2021)
Hailemichael Kindie Abate, 1 Addisu Taye Abate, 1 Zewdu Baye Tezera, 1 Debrewok Tesgera Beshah, 2 Chilot Desta Agegnehu, 3 Mohmmed Adem Getnet, 1 Birhaneselassie Gebeyehu Yazew, 1 Mahlet Temesgen Alemu, 2 Chilot Kassa Mekonenn, 1 Chanyalew Worku Kassahun 1 1Department of Medical Nursing, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Department of Surgical Nursing, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3Community Nursing Unit, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Hailemichael Kindie Abate Tel +251965321790Email haile206k@gmail.comIntroduction: Nursing professionalism is how nurses view their work and is a guide for the behavior of nurses in practice to ensure patient safety and quality care. Poorly perceived nursing professionalism can lead to poor patient outcomes, which decrease the promotion and career options of nurses.Objective: The aim of this study is to assess the perceived prevalence of nursing professionalism among nurses in Public Referral Hospitals of West Amhara Regional State, Ethiopia.Methods: An institution-based cross-sectional study was conducted among 423 nurses from January to February 2021. A simple random sampling method was used to reach the study subject. A self-administered questionnaire was used for data collection. To explain the study variables, frequency tables and percentages were used. A binary and multiple logistic regressions were conducted to see the relation between the dependent variable and independent variables.Results: A total of 407 nurses participated in the study with a response rate of 99.3%. The overall prevalence of good perceived nursing professionalism was found to be 24.8%. Variables such as having > 10 years experience (adjusted odds ratio (AOR)=1.2, 95%CI: 2.9– 5.57) a day working shift (AOR=2.36, 95%CI: 0.78– 6.67), having professional identification (AOR=5.44, 95%CI: 4.38– 8.45), and getting medical service (AOR=1.23, 95%CI: 1.11– 2.28) were significantly associated with perceived good nursing professionalism.Conclusion: The findings of this study showed that only one-fifth of nurses had perceived good nursing professionalism. In this study, variables such as nursing experience > 10 years, working shift, having professional identification, and getting medical services were significantly associated with good perceived nursing professionalism. The policymakers ought to incorporate free medical services to enhance the attitude of nurses toward nursing professionalism.Keywords: nursing, professionalism, hospital, Ethiopia